2015
DOI: 10.1007/978-3-319-06590-8_136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unbalanced Rotor on the Dynamics of Cylindrical Roller Bearings

Abstract: In present study, the non-linear dynamic behavior of a rigid-unbalanced rotor supported on cylindrical roller bearing is analyzed. An analytical model of the rotor-bearing system is developed for the investigation. The Hertzian contact between the bearing components and the clearance are considered as source of nonlinearities in the study. The contact between the rolling elements and races is model using nonlinear spring-mass system. Stiffness of nonlinear spring is calculated by Hertzian elastic contact defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The stress is mainly concentrated on the contact zone between the inner ring and rollers. [38][39][40] The inner raceway surface is flattened by the glass rollers (Fig. 13 b).…”
Section: Failure Simulationmentioning
confidence: 99%
“…The stress is mainly concentrated on the contact zone between the inner ring and rollers. [38][39][40] The inner raceway surface is flattened by the glass rollers (Fig. 13 b).…”
Section: Failure Simulationmentioning
confidence: 99%
“…The results showed that permutation entropy can effectively diagnose and detect the dynamic changes and characterize the bearing operating conditions. Sharma et al 123,124 have employed Poincare´maps and other response plots for the stability analysis of the healthy unbalanced rotor-bearing system, equipped with cylindrical roller bearings. The authors analyzed the responses of the system over a wide range and the results showed that the dynamic behavior of the system is sensitive to small variations of the system parameters and Poincare´maps can be used for common analysis of the system.…”
Section: Nonlinearity Analysis Techniquesmentioning
confidence: 99%
“…Gupta et al [29] also utilized Lyapunov exponent as a quantitative measure of chaos in their study and concluded that, in some of the considered cases, Lyapunov exponent is the only tool to observe the nature of the rotor-bearing system. Sharma et al [30] developed an analytical model of the rotor-bearing system for the investigations of nonlinear vibrations. The authors employed Poincaré maps for the analysis of unstable regimes and summarized the nature of the system at various rotational speeds.…”
Section: Introductionmentioning
confidence: 99%